Artistic research in the visual arts: study of three cases at the University of Costa Rica. - Zúñiga Salas, Xiomara (2015)
This article inquires about the concept of artistic research in visual arts from the study of the work of three Costa Rican artists associated to the University of Costa Rica: Elizabeth Thompson, José Pablo Ureña and Alberto Murillo. In the process, we briefly review the following three approaches to the concept: artistic research about visual arts, artistic research within the arts and artistic research for the arts. Also, we analyze the ontological, the epistemological and the methodological questions proposed by Henk Borgdorff (2006), based on the contributions of the interviewed artists, in order to define the scope of artistic research from others alike. Finally, we propose an approximation to the concept of artistic research in visual arts.